Diagnosis and treatment of bacterial meningitis in the newborn - Ogunlesi TA (Nigerian Journal of Paediatrics, 2024)
Background: Bacterial meningitis in the newborn is globally renowned for high mortality. The associated morbidities also include audiologic, motor, visual and mental deficits.